SUSTAINABLE FASHION DESIGN: EXPLORING THE POTENTIAL OF FABRIC RECONSTRUCTION TECHNIQUES IN CREATING ONE-PIECE DRESSES - Kaur, Jasleen; Ms. Kirti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research investigates the innovative application of fabric reconstruction techniques to design stylish and sustainable one-piece dresses, addressing the growing environmental challenges posed by the fashion industry. The industry, though renowned for its creativity and self-expression, significantly contributes to ecological issues such as textile waste and excessive resource consumption. Fabric reconstruction offers a promising solution by repurposing discarded garments into fashionable new designs, thereby reducing waste and promoting resource efficiency. The study focused on college-going girls as the target demographic, aiming to understand their preferences and acceptance of reconstructed garments compared to conventional clothing. Data was collected using structured questionnaires, capturing insights into their buying behaviour, opinions on sustainability, and perceptions of the reconstructed dresses. The research highlighted the shift in consumer behaviour toward eco-friendly clothing, as participants demonstrated a high level of acceptance and appreciation for the reconstructed designs. Key attributes such as creativity, uniqueness, and quality were particularly valued, indicating a strong potential for these garments to gain traction in the market. Furthermore, the study underscores the importance of fabric reconstruction as a sustainable practice in the fashion industry, emphasizing its role in reducing textile waste while offering innovative design solutions. The findings also highlight the critical need for increased consumer awareness and education about the benefits of reconstructed clothing. Promoting this understanding can pave the way for broader market acceptance and adoption of sustainable fashion practices. Ultimately, this research contributes valuable insights into how sustainable design can reshape the fashion industry and align with the growing demand for environmentally conscious choices.